"Hands off my meter!" when municipalities resist smart meters: Linking arguments and degrees of resistance. (September 2020) - Chamaret, Cécile; Steyer, Véronique; Mayer, Julie C.
Abstract: Despite smart meters are depicted as a core innovative device to support the clean energy transition, their roll-out is facing a growing resistance, not only from final users but also from an unexpected intermediary actor, such as municipalities in France. While previous research has considered intermediaries as a trigger for implementing new technologies, this article examines intermediary resistance. We study the case of municipalities' resistance in France by using a quantitative clustering analysis on 444 municipalities' reports, which detail their decision to reject smart meters. Findings reveal five argumentative strategies of resistance, which are associated to distinct degrees of resistance. Those results challenge previous research by inviting to study resisting actors as a heterogeneous group, and to further explore the particularities of the intermediary level of resisting actors. Our study also shed light on a trigger for resistance that has been neglected in the existing literature: the installation process itself and its potential flaws. Finally, we provide insights to overcome resistance for smart-meters in a context of "forced adoption", by involving intermediary actors in all stages of the roll-out and adopting a differentiated strategy of communication toward them and also by reducing the imbalance between costs and benefits for end-consumers. Highlights: Resistance can be directed against people imposing or installing the technology. Five different profiles of resisting municipalities are found. Ecological and ownership arguments are more likely to urge the strongest forms of resistance. The discourses of resistance are geographically determined. Intermediary actors should be addressed when fighting against resistance.